2022
DOI: 10.7759/cureus.22931
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Operative Time and Blood Loss With the FFX® Device Versus Pedicle Screw Fixation During Surgery for Lumbar Spinal Stenosis: A Retrospective Cohort Study

Abstract: BackgroundPedicle screw (PS) placement can be associated with soft tissue damage and blood loss. The study objective was to evaluate differences in operative time and blood loss between PS fixation and an implantable facet fusion device in patients undergoing lumbar fusion surgery. Materials and methodsA retrospective analysis was performed on patients undergoing lumbar fusion surgery with PS fixation or the lumbar Facet FiXation (FFX) device. Procedures were performed by the same surgeon at a single instituti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…A recent non-randomized, retrospective study compared mean operative time and estimated blood loss between patients undergoing posterior lumbar fusion surgery for LSS with either pedicle screw fixation or the FFX device. 16 The author reported that PS fixation was associated with significantly longer mean operative time compared to placement of the FFX device (152.5 ± 39.4 vs. 99.4 ± 44.0 minutes; p<0.001). Mean operative blood loss was also significantly greater for PS vs. FFX procedures (446.5 ± 272.0 vs. 251.0 ± 315.9 mL; p<0.001).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…A recent non-randomized, retrospective study compared mean operative time and estimated blood loss between patients undergoing posterior lumbar fusion surgery for LSS with either pedicle screw fixation or the FFX device. 16 The author reported that PS fixation was associated with significantly longer mean operative time compared to placement of the FFX device (152.5 ± 39.4 vs. 99.4 ± 44.0 minutes; p<0.001). Mean operative blood loss was also significantly greater for PS vs. FFX procedures (446.5 ± 272.0 vs. 251.0 ± 315.9 mL; p<0.001).…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have reported positive one-year outcomes associated with the placement of the FFX facet fixation device and reduced operative time and blood loss associated with the placement of the implant compared to placement of PS in patients with LSS. 15,16 A finite element simulation comparing the device with the PS placement suggests facet fusion leads to lower mechanical loads at the adjacent levels potentially lowering the risk of adjacent segment degeneration prior to fusion while providing equivalent stability once fusion is achieved. 17 In order to assess the long-term performance of the FFX device and to compare these outcomes with PS fixation, we conducted a hybrid retrospective-prospective study to evaluate clinical and radiological outcomes associated with single or multi-level use of these devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation